The enterprising barrister : organisation, culture and changing professionalism - Goulandris, Atalanta (Oxford ; Hart, 2020)
"What is it like working as a barrister in the 21st century? The independent Bar has transformed in the last 30 years into a commercialised, enterprising profession. Based on interviews with and observation of barristers and chambers' staff, this book identifies key changes that have taken place at the Bar and how these are reshaping and reformulating barristers' professionalism and working culture. Readers are provided with the first empirical overview of the depth, scope and effects of a multi-faceted reform programme that has been imposed on the profession and explores how practitioners have responded. It analyses how this once unified profession has fragmented, as the lived experiences of barristers in different practice areas have diverged. Highly specialised sets of chambers now operate like businesses, whilst others, who are dependent on legal aid funding, struggle to survive. This book offers a unique examination of different sites of change: how the chambers model has evolved, how entrepreneurial barristers market themselves, how aspirant law students prepare to enter the profession and how regulatory and procedural reforms have imposed managerial constraints on practitioners. The conclusion considers what the far-reaching changes mean for the prospects of the Bar in England and Wales"--
The Enterprising Barrister -- Old Bar, New Bar : Reforming the Profession -- The Business of Chambers -- Getting in, Fitting in : The Enterprising Aspiring Barrister -- Getting Work : The New Marketeers -- Direct Access -- Bar Culture -- Community, Unity and Fragmentation -- Conclusion : A New Bar, with a New Kind of Barrister? .
Based on author's thesis (doctoral - City, University of London, Department of Sociology, 2017) issued under title: Continuity and change : the professional lives and culture of self-employed barristers in England and Wales.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Practice of law -- England; Lawyers -- England -- Marketing; Practice of law -- Economic aspects -- England; Law & society; Electronic books